Combined modes of gradual change: the case of academic upgrading and declining collectivism in German skill formation. (10th January 2017) - Graf, Lukas
Abstract: The corporatist-governed dual-training system has been a key example of collective governance in the German capitalist model. However, high-end dual-training is increasingly being offered within post-secondary higher education. Here, firms and universities, not chambers of commerce or trade unions, are the actors negotiating the curricula of and access to a range of 'dual-study programmes'. This article traces the emergence and expansion of this more firm-specific skills provision system, which diminishes the beneficial constraints for strategic cooperation and, in turn, the provision of collective training standards and transferable skills. The case study builds on the 'gradual institutional change' taxonomy, while pointing to the potential benefits of using different modes of change in combination. Through analysing firms' strategies to initiate change in an institutional grey area between established socio-economic spheres, the article shows how layering, conversion and drift can become interlinked and how each individual process can trigger and feed the next.